2021
DOI: 10.1038/s41598-021-84715-7
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, prospective, observational study to determine association of mesangial C1q deposition with renal outcomes in IgA nephropathy

Abstract: It was reported that histopathologic lesions are risk factors for the progression of IgA Nephropathy (IgAN). The aim of this study was to investigate the relationships between mesangial deposition of C1q and renal outcomes in IgAN. 1071 patients with primary IgAN diagnosed by renal biopsy were enrolled in multiple study centers form January 2013 to January 2017. Patients were divided into two groups: C1q-positive and C1q-negative. Using a 1: 4 propensity score matching (PSM) method identifying age, gender, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
1
11
1
Order By: Relevance
“…In this study, we found that posttransplantation recurrent IgAN patients had a significantly higher rate of mesangial C1q positivity compared with patients with native IgAN and that the C1q-positive patients had a higher rate of crescent formation. These findings indicate that mesangial C1q deposition may trigger a sustained inflammatory response that induces endothelial proliferation and crescent formation, as reported previously [10]. Thus, C1q deposition may be an indicator of more advanced disease activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we found that posttransplantation recurrent IgAN patients had a significantly higher rate of mesangial C1q positivity compared with patients with native IgAN and that the C1q-positive patients had a higher rate of crescent formation. These findings indicate that mesangial C1q deposition may trigger a sustained inflammatory response that induces endothelial proliferation and crescent formation, as reported previously [10]. Thus, C1q deposition may be an indicator of more advanced disease activity.…”
Section: Discussionsupporting
confidence: 87%
“…Little is known about the significance of mesangial C1q deposition, which is the first subcomponent of the C1 complex in the classical pathway. Recently, mesangial C1q deposition was found to be associated with treatment failure in native IgAN patients [8] and to predict poor kidney outcomes in both native IgAN [9, 10] and posttransplantation recurrent IgAN [11] patients, highlighting the importance of the classical pathway in the pathogenesis of IgAN. Therefore, we performed a retrospective case-control study to investigate the relationships of mesangial C1q deposition with clinicopathological features and kidney outcomes in both KTRs with recurrent IgAN and patients with native IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…There are no studies on C1q deposition of IgAN in DS. On the other hand, the rate of C1q deposition has been reported to be 2–13.54% in native IgAN and 15.7% in transplanted IgAN, respectively [16, 17]. In one recent report, 13.54% of patients with IgAN were C1q positive and the rate of progression to ESKD was significantly higher in these cases than in C1q-negative cases ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In one recent report, 13.54% of patients with IgAN were C1q positive and the rate of progression to ESKD was significantly higher in these cases than in C1q-negative cases ( p < 0.05). Moreover, C1q-positive cases showed higher rates of endocapillary hypercellularity, tubular atrophy, interstitial fibrosis, and cellular and fibrocellular crescents compared to C1q-negative cases [17]. Another report demonstrated that mesangial C1q deposition, urinary protein, and the estimated glomerular filtration rate are independent predictors of graft failure in cases of kidney transplantation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The complement-activation pathway in IgAN is mainly alternative and lectin pathways rather than classical pathway. Of note, several recent studies have emphasized mesangial C1q deposition, which is rare in native IgAN but relatively frequent in recurrent IgAN, and may predict a poor outcome of kidney transplantation in native and recurrent IgAN cases [17][18][19]. Future research is needed to determine the effects of mesangial C1q deposition on recurrence and progression of IgAN.…”
Section: Risk Factors For Recurrence and Progression Of Iganmentioning
confidence: 99%